Criteria for Optimizing the Capital Structure When Increasing the Value of Joint Stock Companies (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The capital structure of a joint stock company plays a critical role in determining its financial strength and overall value in the eyes of investors and stakeholders. This article examines various optimization criteria that can be used to maximize shareholder value through strategic capital structure decisions. Through a review of existing literature and empirical studies, this study aims to comprehensively explain the main factors influencing the formation of capital structure and their impact on company value.